Construction validity in equilibrium tests: chronological order in tasks presentation - Carolina Silveira; Marcos Trindade Pinheiro Menuchi; Carolina Sant'Ana Simões; Duarte Caetano; Lilian Bucken Gobbi (Universidade Federal de Santa Catarina, 2006)
The equilibrium tests of the Rosa Neto1 Motor evelopment Scale are constituted by ten tasks related to the chronological ages from 2 to 11 years and they determine the participants Motor Age. The tests presentation order is crescent from the child chronological age and the motor age is based on the success or failure in each task. The aim of this study was to analyze the construction validity of the equilibrium motor tests observing the ordering the levels of task difficulty. 76 children with 6 to 9 years of chronological age participated and were assigned in two groups: control group, tests presentation in increased order; and inverted group, tests presentation in decreased order. The results did not revealed statistical significant differences between groups, which indicatethat the presentation order of the tests did not interfere in the children performance, independently of the chronological age. Low success rates occurred in some specific tasks followed by success in advanced tasks. As the results revealed that the participants could perform the tasks after that in which the failure happened the motor age ascribed by the Motor Development Scale can underestimate the children motor development. The variation of the children performance in the tasks suggests that the motor development process is nonlinear. The equilibrium motor tasks purposed in the Motor Development Scale show construction validity. RESUMO Os testes de equilíbrio da Escala de Desenvolvimento Motor de Rosa Neto1 são constituídos por dez tarefas correspondentes às idades cronológicas de 2 a 11 anos e determinam a Idade Motora dos participantes. A ordem de apresentação dos testes é crescente, partindo da idade cronológica da criança e a idade motora baseia-se no sucesso ou fracasso em cada tarefa. O objetivo deste estudo foi analisar a validade de construção dos testes motores em equilíbrio, observando a ordenação e os graus de dificuldade da tarefa. Participaram 76 crianças, com idade cronológica de 6 a 9 anos, que foram distribuídas em dois grupos: grupo controle, aplicação dos testes em ordem crescente; grupo invertido, aplicação dos testes em ordem decrescente. Os resultados não apresentaram diferenças estatisticamente significativas no desempenho entre os grupos, indicando que a ordem de apresentação dos testes não interferiu no desempenho das crianças, independente da idade cronológica. Baixas taxas de sucesso ocorreram em algumas tarefas específicas, seguidas por sucesso em tarefas posteriores. Como os resultados demonstraram que os participantes conseguem executar tarefas seguintes à tarefa em que houve o fracasso, a idade motora apontada pela Escala de Desenvolvimento Motor pode estar subestimando o desenvolvimento motor dessas crianças. A variação do desempenho das crianças nos testes sugere que o processo de desenvolvimento motor é não linear. As tarefas motoras em equilíbrio propostas na Escala de Desenvolvimento Motor apresentam validade de construção.